Sustainable collaboration on complex problems: a “who” not a “what” challenge - Gibson, Josie (Frontiers in Research Metrics and Analytics, 2023)
Despite decades of collective efforts and millions of dollars of cross-sector investment, collaborations created to address wicked problems—complex issues that span industries and sectors whose root causes are unclear—have had mixed success. The wicked problems terrain is tribal and competitive. It is contested by proponents of competing collective change and innovation tools and methodologies, advocates of different leadership approaches and, in recent years, big business champions who claim private enterprise is the most effective driver of solutions. This perspective article argues that while all these elements deserve attention, the primary focus of many collaborations reflects a Western scientific bias toward “what” and “how” questions—governance, processes, activities, metrics and outcomes—at the expense of the “who” component: the human relationships, or relational infrastructure, required to build and sustain effective collective efforts. This is crucial given the grueling realities of complex multi-year initiatives. This article explores the tension between this bias and the need to develop robust relational networks through skilful collective leadership, as reflected in numerous First Nations knowledge practices. We discuss leadership as a both an individual and a collective capability and highlight the need for better understanding of its significant role in anchoring, shaping and guiding effective system-based efforts that achieve positive impact.